2016
DOI: 10.1038/ncomms10246
|View full text |Cite
|
Sign up to set email alerts
|

Isotope dependence of the Zeeman effect in lithium-like calcium

Abstract: The magnetic moment μ of a bound electron, generally expressed by the g-factor μ=−g μB s ħ−1 with μB the Bohr magneton and s the electron's spin, can be calculated by bound-state quantum electrodynamics (BS-QED) to very high precision. The recent ultra-precise experiment on hydrogen-like silicon determined this value to eleven significant digits, and thus allowed to rigorously probe the validity of BS-QED. Yet, the investigation of one of the most interesting contribution to the g-factor, the relativistic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 47 publications
(74 reference statements)
7
113
1
2
Order By: Relevance
“…This causes another systematic deviation of the extracted cyclotron frequency and modifies the measured g-factor by (δ g/g) im = + 0.04 p.p.b., the error of this value being on the sub-p.p.t. level 33,34 .…”
Section: Methodsmentioning
confidence: 99%
“…This causes another systematic deviation of the extracted cyclotron frequency and modifies the measured g-factor by (δ g/g) im = + 0.04 p.p.b., the error of this value being on the sub-p.p.t. level 33,34 .…”
Section: Methodsmentioning
confidence: 99%
“…Первый расчет этого вклада во всех порядках по αZ был выполнен в работе [44] для состояния 1s. Для состояния 2s расчеты были выполнены в работе [15] для литиеподобного кальция и в работах [16,17] …”
Section: результаты и обсуждениеunclassified
“…Еще более нетривиальная проверка КЭД связана с эффектом отдачи ядра, полное описание которого требует выхода за рамки картины Фарри, т. е. за рамки приближения внешнего поля. В частности, измерение изотопического сдвига для g-фактора литиеподобного кальция [15] позволило непосредственно наблюдать вклад эффекта отдачи. В на-шей недавней работе [16] двухэлектронный вклад в этот эффект был вычислен заново в рамках релятивистско-го подхода, что позволило улучшить согласие между теорией и экспериментом.…”
Section: Introductionunclassified
“…Several mass measurements have shown that the novel method provides a forty times higher mass resolving power and a gain in precision by a factor of about five compared to the conventional scheme [27]. The new method has been applied to mass difference measurements of stable and long-lived nuclides, for example 163 Ho and 48 Ca, reaching uncertainties of tens of electronvolts [29,30]. For the application to the heaviest elements in the context of nuclear structure studies uncertainties of a few keV suffice.…”
Section: Nobel Symposium Ns160 -Chemistry and Physics Of Heavy And Sumentioning
confidence: 99%